THE PIVOTAL ROLE OF KNOWLEDGE STRUCTURE AND INSTRUCTIONAL DESIGN IN THE DEVELOPMENT OF TEACHERS TEACHING MATHEMATICS TO STUDENTS WITH SPECIAL NEEDS (Proceedings of International Conference on Special Education, 2017)
Teaching for Mathematising, rested upon the notion of “mathematising” first coined by prominent mathematics educator Hans Freudenthal, is an ongoing developmental project that started in Hong Kong in 1998. Originally, it was an attempt to improve mathematics teaching in the general elementary schools. Recently, the instructional designs developed over the years were applied and adapted to help students with special educational needs. The spectrum of application ranges from inclusive education to special education. In this paper, how teacher development is carried out based on instructional designs and the ideas behind will be reported. Besides, how knowledge structure impacts the creation of instructional designs will also be discussed.